Studi Kinerja Fresh Water Generator Di Kapal AHTS PETEKA 5401: Iing Mustain, Abdurohman, Haris Rahmanto - Abdurohman; Iing Mustain; Haris Rahmanto (LPPM AKMI SUAKA BAHARI CIREBON, 2019)
Fresh water is one of the primary needs on board. Shortage of fresh water on board, has a considerable risk, and to overcome the problem of lack of fresh water, commercial vessels are generally equipped with fresh water generators where the aircraft works with the process of evaporating seawater in the evaporator and seawater vapor is cooled with the way condensation in the distillation plane to produce fresh water. The fresh water genertaor parts are Evaporator, Condenser, Demister, Water ejector, Ejector Pump, and Destillate Pump. Then the Cause of Declining Freshwater Production in Fresh Water Generators is a decrease in fresh water production in fresh water generators. As for how to overcome so that the production of fresh water produced by fresh water generators does not decrease ie when the evaporator plate is cleaned, make sure the gasket on the plate must be in good condition, then cleaned from the crust attached to the plate, once every six months the nozzle and diffuser ( throwers) are removed and examined. And check the ejector pump for leaks and from corrosion such as impellers, casings, rings and shafts. In generating data the author uses descriptive research that is used to find the broadest possible knowledge of the object of research at a particular time. Descriptive research is research whose purpose is to explain or describe an event, condition, object whether a person, or everything related to variables that can be explained using either numbers or words. Keywords : Fresh Water Generator, Evaporator, Ejector Pump Air tawar merupakan salah satu kebutuhan primer di atas kapal. Kekurangan air tawar di atas kapal, mempunyai resiko yang cukup besar, dan untuk mengatasi masalah kekurangan air tawar, kapal-kapal niaga pada umumnya dilengkapi dengan fresh water generator dimana pesawat ini bekerja dengan proses menguapkan air laut di dalam evaporator dan uap air laut didinginkan dengan cara kondensasi di dalam pesawat destilasi sehingga menghasilkan air tawar. Bagian-bagian fresh water genertaor adalah Evaporator, Kondensor, Demister, Air ejektor, Pompa ejektor, dan Pompa destillate. Kemudian Penyebab Menurunnya Produksi Air Tawar Pada Fresh Water Generator adalah menurunnya produksi air tawar pada fresh water generator. Adapun cara mengatasi agar produksi air tawar yang di hasilakan fresh water generator tidak menurun yaitu pada saat plat evaporator dibersihkan, pastikan gasket pada plat harus dalam kondisi baik, kemudian dibersihkan dari kerak-kerak yang menempel pada plat, setiap enam bulan sekali nozzle dan difuser (penyembur) dilepas dan diperiksa. Dan periksa pompa ejektor dari kebocoran dan dari korosi seperti impeller, casing, ring, dan shaft. Dalam menghasilkan data penulis menggunakan penelitian deskriptif yang digunakan untuk menemukan pengetahuan yang seluas-luasnya terhadap objek penelitian pada suatu masa tertentu. Penelitian deskriptif adalah penelitian yang tujuannya untuk menjelaskan atau mendeskripsikan suatu peristiwa, keadaan, objek apakah orang, atau segala sesuatu yang terkait dengan variabel-variebel yang bisa dijelaskan baik menggunakan angka-angka maupun kata-kata. Kata Kunci : Fresh Water Generator, Evaporator, Pompa Ejektor